2011
DOI: 10.1002/eat.20965
|View full text |Cite
|
Sign up to set email alerts
|

Comorbidity of partial and subthreshold ptsd among men and women with eating disorders in the national comorbidity survey‐replication study

Abstract: Objective The comorbidity of posttraumatic stress disorder (PTSD) and eating disorders (EDs) is high among women but has been understudied in men. Little is known about the association between partial or subthreshold PTSD and EDs among women or men. Method This study included PTSD and ED data from male (n=2382) and female (n=3310) National Comorbidity Survey-Replication study participants. Results The vast majority of women and men with anorexia nervosa (AN), bulimia nervosa (BN), and binge eating disorder… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

21
167
1
4

Year Published

2014
2014
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 208 publications
(193 citation statements)
references
References 49 publications
(62 reference statements)
21
167
1
4
Order By: Relevance
“…Partner's response to the pregnancy was reported by women themselves; therefore, results including this variable might be due to shared method variance. A high prevalence of interpersonal trauma and PTSD has been observed among women with ED, and both depression and anxiety are known to be highly comorbid with an ED diagnosis, all of which may also increase vulnerability for IPV 37. Women with ED are known to suffer from high comorbidity; therefore, adjusting for this would result in unrepresentative findings applicable to only a subgroup of women who have experienced ED only, without comorbidity.…”
Section: Discussionmentioning
confidence: 99%
“…Partner's response to the pregnancy was reported by women themselves; therefore, results including this variable might be due to shared method variance. A high prevalence of interpersonal trauma and PTSD has been observed among women with ED, and both depression and anxiety are known to be highly comorbid with an ED diagnosis, all of which may also increase vulnerability for IPV 37. Women with ED are known to suffer from high comorbidity; therefore, adjusting for this would result in unrepresentative findings applicable to only a subgroup of women who have experienced ED only, without comorbidity.…”
Section: Discussionmentioning
confidence: 99%
“…Although they do not share core criteria, numerous features of ED and PTSD overlap (Mitchell, Mazzeo, Schlesinger, Brewerton & Smith, 2012), some of which are discussed below, including trauma history, dissociation, and avoidance.…”
Section: Commonalities Between Ed and Ptsdmentioning
confidence: 99%
“…The majority of research evidence suggests that trauma histories are more often associated with ED with bulimic symptoms such as BN, AN binge-purge type, BED or EDNOS with bulimic features than with AN restricting type or EDNOS not associated with bulimic symptoms (Brewerton, 2004(Brewerton, , 2005(Brewerton, , 2006Grilo & Masheb, 2002;Wonderlich et al, 1997). For example, with data from the National Comorbidity Replication Study with both male (n = 2382) and female (n = 3310) participants, Mitchell et al (2012) demonstrated the rates of nearly all trauma types assessed were higher among participants with BN and BED, compared with the general population. This finding was particularly salient regarding interpersonal traumas suggesting that men and women with ED have high rates of trauma perpetrated by others, especially those participants with BN and BED.…”
Section: Trauma Historymentioning
confidence: 99%
See 2 more Smart Citations